A framework for modeling and simulating Aedes aegypti and dengue fever dynamics - Lima, Tiago; Carneiro, Tiago; Silva, Leandro; Lana, Raquel; Codeco, Claudia; Reis, Izabel; Maretto, Raian; Santos, Leonardo; Monteiro, Antonio M.V.; Medeiros, Liliam [UNESP]; Coelho, Flavio (Ieee, 2014)
Dengue fever represents a great challenge for many countries, and methodologies to prevent and/or control its transmission have been largely discussed by the research community. Modeling is a powerful tool to understand epidemic dynamics and to evaluate costs, benefits and effectiveness of control strategies. In order to assist decision-makers and researchers in the evaluation of different methodologies, we developed DengueME, a collaborative open source platform to simulate dengue disease and its vector's dynamics. DengueME provides a series of compartmental and individual-based models, implemented over a GIS database, that represents the Aedes aegypti's life cycle, human demography, human mobility, urban landscape and dengue transmission. The platform is designed to allow easy simulation of intervention scenarios. A GUI was developed to facilitate model configuration and data input.